Microbial assessment of pathogenic bacterial growth in ice cream and kulfa. Issue 12 (23rd October 2018) - Shaheen, Shabnum; Jaffer, Mehwish; Aslam, Barira; Hussain, Khadim; Khan, Asaf; Ashfaq, Muhammad; Ulfat, Mobina; Sardar, Andaleeb Anwar; Ahmad, Mushtaq; Zafar, Muhammad; Khan, Farah
Abstract: Current study was focused to examine the total bacterial count in packed and unpacked ice cream and kulfa collected from 12 different localities of Lahore. The bacterial colonies were isolated and grown on agar‐broth media under sterilized conditions. Serial dilution technique was used to compose the replicates to get total viable count of bacteria. Results in case of packed ice cream samples indicated maximum (618 × 10 –6 CFU/g) and minimum (79 × 10 –6 CFU/g) bacterial count while in case of unpacked ice cream samples maximum and minimum bacterial count was 163 × 10 –6 CFU/g and 71 × 10 –6 CFU/g, respectively. Whereas in case of packed kulfa samples, maximum and minimum recorded bacterial count was 163 × 10 –6 CFU/g and 72 × 10 –6 CFU/g, respectively. The LM and SEM of the isolated bacteria were also performed for correct identification. Results indicated that the total bacterial count recorded in the samples exceeded the standard tolerable range which can lead to serious health damage of consumers. Abstract : Bacterial isolation from bakery products. Bakery products of Lahore, Pakistan is investigated first time on the basis of LM and SEM and found very significant to check the quality of bakery products or not.